Rescue Paracetamol in Postoperative Pain Management in Extremely Low Birth Weight Neonates Following Abdominal Surgery: A Single Unit Retrospective Study - Cihlarova, Hana; Bencova, Lenka; Zlatohlavkova, Blanka; Allegaert, Karel; Pokorna, Pavla (Frontiers in pediatrics, 2022)
Background: Intravenous paracetamol added to morphine reduces postoperative morphine consumption in (near)term neonates. However, there are only sparse data on intravenous paracetamol as multimodal strategy in extremely low birth weight (ELBW) neonates. Objectives: This study aims to assess the effects of rescue intravenous paracetamol on postoperative pain management (≤48 h postoperatively) in relation to both analgesic efficacy (validated pain assessment, drug consumption, adequate rescue medication) and safety (hypotension and bradycardia). This rescue practice was part of a standardized pain management approach in a single neonatal intensive care unit (NICU). Methods: A single-center retrospective observational study included 20 ELBW neonates, who underwent major abdominal surgery. The primary endpoints of the postoperative study period were pain intensity, over-sedation, time to first rescue analgesic dose, and the effect of paracetamol on opiate consumption. Secondary endpoints were safety parameters (hypotension, bradycardia). And as tertiary endpoints, the determinants of long-term outcome were evaluated (i.e., duration of mechanical ventilation, intraventricular hemorrhage - IVH, periventricular leukomalacia - PVL, postnatal growth restriction, stage of chronic lung disease - CLD or neurodevelopmental outcome according to Bayley-II Scales of Infant Development at 18-24 months). Results: All neonates received continuous opioids (sufentanil or morphine) and 13/20 also intravenous paracetamol as rescue pain medication during a 48-h postoperative period. Although opioid consumption was equal in the non-paracetamol and the paracetamol group over 48 h, the non-paracetamol group was characterized by oversedation (COMFORTneo < 9), a higher incidence of severe hypotension, and younger postnatal age (p < 0.05). All long-term outcome findings were similar between both groups. Conclusions: Our study focused on postoperative pain management in ELBW neonates, and showed that intravenous paracetamol seems to be safe. Prospective validation of dosage regimens of analgesic drugs is needed to achieve efficacy goals.